Understanding the effects of hydraulic fracturing flowback and produced water (FPW) to the aquatic invertebrate, Lumbriculus variegatus under various exposure regimes. (April 2020) - Mehler, W. Tyler; Nagel, Andrew; Flynn, Shannon; Zhang, Yifeng; Sun, Chenxing; Martin, Jonathan; Alessi, Daniel; Goss, Greg G.
Abstract: Hydraulic fracturing of horizontal wells is a cost effective means for extracting oil and gas from low permeability formations. Hydraulic fracturing often produces considerable volumes of flowback and produced water (FPW). FPW associated with hydraulic fracturing has been shown to be a complex, often brackish mixture containing a variety of anthropogenic and geogenic compounds. In the present study, the risk of FPW releases to aquatic systems was studied using the model benthic invertebrate, Lumbriculus variegatus and field-collected FPW from a fractured well in Alberta. Acute, chronic, and pulse toxicity were evaluated to better understand the implications of accidental FPW releases to aquatic environments. Although L. variegatus is thought to have a high tolerance to many stressors, acute toxicity was significant at low concentrations ( i.e. high dilutions) of FPW (48 h LC50: 4–5%). Chronic toxicity (28 d)of FPW in this species was even more pronounced with LC50s (survival/reproduction) and EC50s (total mass) at dilutions as low as 0.22% FPW. Investigations evaluating pulse toxicity (6 h and 48 h exposure) showed a significant amount of latent mortality occurring when compared to the acute results. Additionally, causality in acute and chronic bioassays differed as acute toxicity appeared to be primarily driven by salinity, which was not the case for chronic toxicity, as other stressors appear to be important as well. The findings of this study show the importance of evaluating multiple exposure regimes, the complexity of FPW, and also shows the potential aquatic risk posed by FPW releases. Graphical abstract: Image 1 Highlights: FPW dilution >10% caused significant toxicity in minutes to L. variegatus. Flowback and produced water toxicity change with exposure type. Latent mortality to L. variegatus was observed in FPW pulse exposures. Chronic effects to L. variegatus were evident at FPW concentrations as low as 0.1%. High salinity and low dissolved oxygen are drivers of FPW chronic toxicity. Abstract : Hydraulic fracturing waste showed significant toxicological effects to Lumbriculus variegatus under acute, pulse, and chronic exposures.